2018
DOI: 10.1007/s00586-018-5724-8
|View full text |Cite
|
Sign up to set email alerts
|

The Global Spine Care Initiative: classification system for spine-related concerns

Abstract: An international and interprofessional group developed a comprehensive classification system for all potential presentations of people who may seek care or advice at a spine care program. This classification can be used in the development of a spine care pathway, in clinical practice, and for research purposes. This classification needs to be tested for validity, reliability, and consistency among clinicians from different specialties and in different communities and cultures. These slides can be retrieved und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 25 publications
0
34
0
Order By: Relevance
“…Thirty-nine VA DCs served as consensus panelists (35% response rate). Demographic characteristics (Table 1) included a mean (standard deviation) age of 46 (11) years, 17 (11) years of clinical experience in chiropractic, and 5 (5) years employed as a VA chiropractor. Over 50% of panelists reported prior involvement in a Delphi consensus study, 77% reported using a decision aid in practice, and 92% reported using tissue-specific diagnoses to characterize LBP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-nine VA DCs served as consensus panelists (35% response rate). Demographic characteristics (Table 1) included a mean (standard deviation) age of 46 (11) years, 17 (11) years of clinical experience in chiropractic, and 5 (5) years employed as a VA chiropractor. Over 50% of panelists reported prior involvement in a Delphi consensus study, 77% reported using a decision aid in practice, and 92% reported using tissue-specific diagnoses to characterize LBP.…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7] Several evidence-based classification systems are available to guide diagnostic evaluation. [8][9][10][11] Doctors of chiropractic (DCs), including those employed within US Veterans Affairs (VA) health care facilities, provide nonpharmacologic, multimodal, conservative care primarily for musculoskeletal conditions, most often for LBP. 12 A fast-growing discipline within VA, chiropractic services are available at over 65 clinics nationwide, accounting for over 159,000 patient visits in 2016.…”
Section: Introductionmentioning
confidence: 99%
“…50 One complementary approach to diagnosis is a classification system for spine-related concerns developed by the Global Spine Care Initiative. 51 This system classifies spine-related conditions by symptom characteristics, functional deficits, and severity. The diagnostic process presented in this article provides criteria to help understand the strength of evidence for identifying likely pathophysiological processes underlying these classifications and potentially informing ongoing management decisions.…”
Section: Discussionmentioning
confidence: 99%
“…This was a prospective study comprising 86 consecutive patients who underwent L5-S1 ALIF procedure for lumbo-pelvic discopathy between January 2013 and May 2017. Patients who met all the inclusion criteria-chronic low back pain in relation to an active discopathy with Modic 1 [7] or Pfirrmann 5 [8] signal on the magnetic resonance imaging (MRI), and degenerative lesion of the articular process at the L5-S1 level without arthritis at L4-L5 level-were assigned to two groups. Group 1 (G1) consisted of patients who with isolated L5-S1 level or hybrid surgery (L5-S1 ALIF procedure associated with L4-L5 lumbar disc replacement (LDR), and group 2 (G2) for symptomatic lumbar degenerative disc disease (one or two level) ( Fig.…”
Section: Population Descriptionmentioning
confidence: 99%
“…As well, isolated distal lumbar discopathy, with loss of disc height, can induce segmental lumbo-pelvic kyphosis [3,5,6]. One-or two-level anterior or lateral lumbar interbody fusions can alter segmental LL with or without modification of the lumbo-pelvic kinematic parameters [7]; however, whether this modification can be applied to the preoperative status is not clear.…”
Section: Introductionmentioning
confidence: 99%